Letter from Antonio Salcedo Sahagun to Mayor Jane Tolmach - Antonio Salcedo Sahagun::::::
A letter from Antonio Salcedo Sahagun, Municipal President of the city of Ocotlán, Jalisco, Mexico to Mayor Jane Tolmach accepting an invitation to visit Oxnard, California. Ocotlán and Oxnard are sister cities. Date not provided.